Perceived Difficult Map Reading and Interpretation among Senior Secondary School Geography Students in Katagum Education Zone, Bauchi State-Nigeria - Saleh, Mustapha; Monday, Sampson; Dalhatu, Aliyu H.; Adaugo, Unwuzurike U. (Kashere Journal of Education, 2022)
The study investigated the perception of difficulties in map use among Senior Secondary Geography students, in Katagum Education Zone, Bauchi State, Nigeria. The study was guided by two research questions and two null hypotheses. Descriptive and ex-post facto survey research design were adopted for the study. The population of the study comprised of 11064 Senior Secondary School (SS3) Geography Students (7191 males and 3873 females) in the all government owned senior secondary schools in Katagum Education Zone of Bauchi State during 2020/2021 academic session. The sample size of the study comprises of 386 Senior Secondary three (SS3) students drawn using multi-stage sampling procedure. The instrument for data collection was Geography Difficulty Identification Questionnaire (GDIQ). The instrument was validated by three experts from the Department of Social Science Education, University of Nigeria, Nsukka. An overall reliability coefficient of 0.72 for the instrument was ascertained using Cronbach Alpha. The data collected for the research questions was analyzed using descriptive analysis (mean and standard deviation). The t-test was used to test the hypotheses at p< 0.05 level of significance. The findings of the study revealed that the school location and gender are not a significant factor in determining specific difficulties encountered in map reading and interpretation in geography. Based on these findings, recommendations were made.